2023
DOI: 10.1002/csr.2494
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability reporting in Africa: A systematic review and agenda for future research

Abstract: This study provides a comprehensive systematic review of the sustainability reporting research focused on Africa. Using a systematic literature review approach, we synthesized 179 high‐quality journal articles obtained from the Scopus database. The study revealed that the extent and quality of SDGs and sustainability reporting in Africa are still very low and unsatisfactory. Also, we found that the existing studies mainly concentrated on the determinants of sustainability reporting, while limited research addr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 147 publications
0
0
0
Order By: Relevance
“…The current findings align with previous research by Arora et al (2022), which also emphasised the flexibility of the <IR> Framework in portraying an organisation’s value-creation narrative. Interestingly, this research contrasts with earlier findings that found companies generally reported on only a limited set of specific sustainability issues (Visser, Wayne Africa Merlin-Tao, 2002; Igwe et al , 2023). Instead, the present study indicates that the <IR> Framework enables companies to cover a broader spectrum of sustainability issues, perhaps more attuned to their particular context.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The current findings align with previous research by Arora et al (2022), which also emphasised the flexibility of the <IR> Framework in portraying an organisation’s value-creation narrative. Interestingly, this research contrasts with earlier findings that found companies generally reported on only a limited set of specific sustainability issues (Visser, Wayne Africa Merlin-Tao, 2002; Igwe et al , 2023). Instead, the present study indicates that the <IR> Framework enables companies to cover a broader spectrum of sustainability issues, perhaps more attuned to their particular context.…”
Section: Discussioncontrasting
confidence: 99%
“…These are further exacerbated by the lingering effects of apartheid, leading to social problems that are more profound than those in most other nations (Carels et al , 2013; Haji and Anifowose, 2017; Montecalvo et al , 2018). South African companies, mirroring a trend seen in many other developing countries, often place less emphasis on environmental impacts and provide comparatively limited environmental disclosure (De Villiers and Van Staden, 2006; Igwe et al , 2023). South Africa’s sustainability reporting practices are heavily influenced by its socio-economic challenges (Visser, Wayne Africa Merlin-Tao, 2002), rendering previous research on this subject less applicable to understanding sustainability reporting in more developed countries.…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies on assurance and sustainability reporting in literature. The study of Igwe et al (2023) examined the literature review of SRP in Africa, the authors decried low studies on assurance and sustainability reporting in Africa. However, there are other studies in other countries on this study.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…The limited research that does exist focuses more on sub-continental nations such as Bangladesh (Momin and Parker, 2013), Nigeria (Erin et al , 2021) and Sri Lanka (Dissanayake et al , 2016). Also, the few studies that examined the quality of sustainability reporting neglected the subject of sustainability assurance (Igwe et al , 2023; Erin et al , 2021). Also, in recent times, there has been a call for more research in the area of non-financial reporting in sub-Saharan Africa (Tilt et al , 2021; Wachira and Mathuva, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The conflicting evidence on the relationship between sustainability reporting and financial performance provides an avenue for further interrogations into the matter. Literature show that studies on the subject matter have been sparse in the African context because most firms in Africa have not fully embraced the concept of sustainability reporting (Igwe et al, 2023). This current study therefore used South Africa, which has the most developed sustainability reporting culture in Africa (Tilt et al, 2020), to provide more empirical evidence on the subject from the African perspective.…”
Section: Introductionmentioning
confidence: 99%